Farm land mobility and adjustments in farming in Northern Ireland - Alexander, D. J. (Statistical and Social Inquiry Society of Ireland, 1965)
This paper is about the "mobility" of land as a factor of production in Northern Ireland agriculture. Farm land mobility in the title means all forms of change of control of the use of land within the farm sector in Northern Ireland. The land is agricultural land in the Province, particularly that area returned by farmers as "crops and grass" in the Agricultural Census Adjustments in farming refers to re-allocation of the factors of production between farm business units. This is often called "structural" change in the agricultural economic literature.
Read before the Society, 10 December 1964
Keywords: Agriculture; Factor mobility; Structural change in Northern Ireland agriculture; Northern Ireland; 314.15